Protective or Harmful: The Dual Roles of Autophagy in Diabetic Retinopathy - Gong, Qiaoyun; Wang, Haiyan; Yu, Ping; Qian, Tianwei; Xu, Xun (Frontiers in Medicine, 2021)
Autophagy is a self-degradative pathway involving intracellular substance degradation and recycling. Recently, this process has attracted a great deal of attention for its fundamental effect on physiological processes in cells, tissues, and the maintenance of organismal homeostasis. Dysregulation of autophagy occurs in some diseases, including immune disease, cancer, and neurodegenerative conditions. Diabetic retinopathy (DR), as a serious microvascular complication of diabetes, is the main cause of visual loss in working-age adults worldwide. The pathogenic mechanisms of DR are thought to be associated with accumulation of oxidative stress, retinal cell apoptosis, inflammatory response, endoplasmic reticulum (ER) stress, and nutrient starvation. These factors are closely related to the regulation of autophagy under pathological conditions. Increasing evidence has demonstrated the potential role of autophagy in the progression of DR through different pathways. However, to date this role is not understood, and whether the altered level of autophagy flux protects DR, or instead aggravates the progression, needs to be explored. In this review, we explore the alterations and functions of autophagy in different retinal cells and tissues under DR conditions, and explain the mechanisms involved in DR progression. We aim to provide a basis on which DR associated stress-modulated autophagy may be understood, and to suggest novel targets for future therapeutic intervention in DR.